The prevalence of micro Takaful products in the eyes of Malaysian SMEs - Che Mohd Salleh, Marhanum; Padzim, Fatimah Zaharah (International Academic Institute For Science and Technology; YAMUNANAGAR, HARYANA, INDIA, 2018)
The research examines the level of awareness and understanding among Malaysian SMEs towards Micro Takaful products. It also identifies the differences of awareness and understanding level among the SMEs of different educational background. Data were collected through a survey based on questionnaires among the SME owners in Malaysia. Based on analyses, it is found that the level of awareness and understanding among SMEs in Malaysia towards micro Takaful still at a low level. Besides that, the findings indicate that educational level of SMEs’ owners does impact their level of understanding instead of awareness on Micro Takaful product. Accordingly, the SMEs’ owners who are Degree holders tend to have different understanding compare to other levels of education. Thus, the industry players, especially the operators and their agents should increase their effort to educate the SMEs on future financial protections especially on the features of Micro Takaful products.